Impacts of Ocean Warming on China's Fisheries Catches: An Application of “Mean Temperature of the Catch” Concept - Liang, Cui; Xian, Weiwei; Pauly, Daniel (Frontiers in Marine Science, 2018)
Ocean warming can strongly impact marine fisheries; notably, it can cause the “mean temperature of the catch” (MTC) to increase, an indicator of the tropicalization of fisheries catches. In this contribution, we explore MTC changes in three large marine ecosystems (LMEs) along China’s coasts, i.e., the Yellow Sea, East China Sea, and South China Sea LMEs, and their relationships to shifts of the sea surface temperature (SST). The results show that, while the MTCs began to increase in 1962 in the East China Sea and in 1968 in the Yellow Sea, there was no detectable increase in the South China Sea. There also was a strong relationship between MTC and SST in the Yellow and East China Seas from 1950 to 2010, especially when taking a 3-year time-lag into account. The lack of change of the MTC in the South China Sea is attributed to the relatively small increase in SST over the time period considered, and the fact that the MTC of tropical ecosystems such as the South China Sea is not predicted to increase in the first place, given that their fauna cannot be replaced by another, adapted to higher temperature. Overall, these results suggest that ocean warming is already having an impact on China’s marine fisheries, and that policies to curtail greenhouse gas emissions are urgently needed to minimize the increase of these impacts on fisheries.